Accumulation of intermediate denitrifying compounds inhibiting biological denitrification on cathode in Microbial Fuel Cell. Issue 1 (December 2015) - Al-Mamun, Abdullah; Baawain, Mahad
Abstract Background Bio-cathode denitrifying microbial fuel cell (MFC) is a promising bio-electrochemical system (BES) where both the reactions of anodic oxidation and cathodic reduction are catalyzed by microorganisms. In this nitrogen removal process, a complete biological denitrification from nitrate (NO3 - ) to molecular nitrogen (N2 ) was achieved by four reduction steps, forming nitrite (NO2 − ), nitric oxide (NO) and nitrous oxide (N2 O) as intermediate compounds. These enzymatic catalysis reductions are often slowed down on cathode electrode at the higher cathodic nitrate loading. This study investigated the cause for inhibition of the biological denitrification in a three-chambered MFC where the middle chamber acted as denitrifying bio-cathode and the two chambers at the side acted as bio-anode. Carbon fiber brushes were used as electrodes and nafion membranes were used as separator between the chambers. Results The maximum power obtained was 14.63 W m−3 net cathodic compartment (NCC) (Rext =11.5Ω) at an optimum nitrate loading of 0.15 kg NO3 − -N m−3 NCC d−1 . The accumulation of one of the intermediate denitrifying compound, e.g., NO2 − adversely affected biological denitrification rate on cathode. According to chemical kinetics, the accumulated NO2 − will form free nitrous acid (FNA, HNO2 ) in aqueous chemical system spontaneously. The study showed that approximately 45 % of the current production and 20 % of the total denitrification was decreased at a FNA concentration of 0.0014 ± 0.0001 mg HNO2 – N L−1 with an equivalent nitrite concentration of 6.2 ± 0.9 mg NO2 - - N L−1 . Conclusions The novel biological process indicates the potential of using denitrifying bio-cathode MFC for green energy production.